Hollow ZIFs-derived nanoporous carbon for efficient capacitive deionization. (20th May 2018) - Shen, Jiaming; Li, Yang; Wang, Chaohai; Luo, Rui; Li, Jiansheng; Sun, Xiuyun; Shen, Jinyou; Han, Weiqing; Wang, Lianjun
Abstract: Desalination performance of capacitive deionization (CDI), a promising deionization technology, depends significantly upon the compositions and internal structures of electrode materials. Herein, hollow ZIFs-derived nanoporous carbons (HZCs) were prepared via chemical etching method and subsequent pyrolysis. Particularly, the tannic acid as an etching agent was employed to tailor hollow structure. The resultant HZCs possess high surface area, wide pore size distribution, obvious hollow cavity and high nitrogen content. Moreover, HZCs electrodes exhibited a significantly improved CDI performance over the solid ZIFs-derived nanoporous carbons (SZCs) electrodes. The improved electrosorption rate and capacity (15.31 mg g -1  at 1.2 V) of HZCs electrode imply that hollow structure facilitates the transportation for both ions and mass on CDI process. Besides, the further cycle experiment exhibits a great regeneration stability of HZCs electrode over 20 adsorption-desorption cycles. All these results indicate that HZCs should be a promising candidate for CDI application. Graphical abstract: Hollow ZIFs-derived porous carbons (HZCs) was prepared via chemistry etching method and subsequent pyrolysis, then utilized as CDI electrodes. The as-prepared electrode exhibits excellent capacitive deionization performance and great stability. Highlights: The hollow ZIFs-derived porous carbons (HZCs) as CDI electrodes was simply prepared. HZCs possessed the large surface area and rich mesopores. CDI performance on the as-prepared electrodes shows a high level among the reported carbon electrodes. The improved electrosorption rate and capacity of HZCs electrode proved the superiority of hollow structure on CDI process.